Analysis of Village Funds and Gross Regional Domestic Product Impacts Human Development Index in Naggroe Aceh Darussalam Province - Perangin Angin*, Sutejo; Lubis, Irsad; Tanjung, Ahmad Albar; Yahya, Aiyub (Riwayat: Educational Journal of History and Humanities, 2023)
The principal objective of government-led development is to revive community economy and standard of living. Village Funds is used to finance the entire village authority having priority to support village development programs and village community empowerment. The value of the Gross Regional Domestic Product, the result of gross added value arising from economic activity in the regions, is another means that can have an impact on advancing the economy and the standard of living of its people as well as to encourage villages to grow into prosperous villages. The research design used is quantitative research with time series as panel data analysis, where the variables in this study are Village Funds (X1), Gross Regional Domestic Product (X2), and Human Development Index (Y). The data is obtained by collecting secondary data through the website of the Central Bureau of Statistics for Aceh Province. The results show that the F-count value was 578.7339, and the village fund variable had a positive coefficient of 0.059486 and t-count of 6.294444, gross regional domestic product of 0.087382 with a t-count value of 10.25143 meaning that the two variables have a positive impact on the regional/municipal human development index in the Nanggroe Aceh Darussalam Province. Therefore, it can be concluded that these two variables can increase the human development index in a region.